Quality and nutritional appraisal of guava and soy-infused noodles: Boosting antioxidants and fiber - Mitu Rani Sarker; Md. Jaynal Abedin; Abu Tareq Mohammad Abdullah; Tasnim Farzana (Applied Food Research)
Noodles are a staple food in many cultures in the world, enjoyed by all ages. With increasing health consciousness, there's a growing demand to incorporate health-enhancing ingredients into traditional meals. Soy flour is rich in protein, while guava powder offers dietary fiber, antioxidants, and essential minerals. This study aimed to develop noodles that are rich in antioxidants and fiber by substituting wheat flour with 10 % soy flour and varying amounts of guava powder at 10 %, 20 %, 30 %, and 40 %. To assess the impact of GP and SF integration in developing noodles, the nutritional composition, water activity, color, texture profile, cooking capabilities, antioxidant properties, and sensory qualities were investigated. The addition of GP and SF to noodles significantly (p < 0.05) increased DPPH scavenging activity from 4.96 % to 66.53 %, ferric-reducing antioxidant power from 58.04 % to 90.09 %, total phenolic content from 19.09 mg to 373.08 mg GAE/100 g, and total antioxidant content from 69.38 mg to 1164.17 mg AAE/100 g. It was also noticed that the levels of dietary fiber (8.95 to 26.69 g/100 g), protein (11.17 to 14.11 g/100 g), and essential minerals like calcium, potassium, and zinc went up (p < 0.05). The texture profile analysis revealed a softer and less chewy texture, with no significant changes in springiness or adhesiveness. However, in the sensory evaluation test, noodles with 30 % GP received the highest preference from panelists. This study found that adding 30 % GP to noodles was the most practical way to improve their nutritional value while still causing only minor changes to their color, texture, cooking properties, and sensory qualities. Consequently, our study will contribute to reducing health disparities by enhancing the intake of nutrients and antioxidants in an effective manner.